2002
DOI: 10.1080/15428110208984706
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Databases and Exposure Surveillance: Promise and Practice

Abstract: Based on recent developments in occupational health and a review of industry practices, it is argued that integrated exposure database and surveillance systems hold considerable promise for improving workplace health and safety. A foundation from which to build practical and effective exposure surveillance systems is proposed based on the integration of recent developments in electronic exposure databases, the codification of exposure assessment practice, and the theory and practice of public health surveillan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 37 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…It is not feasible to rely on health outcome surveillance in this context as the mental disorders and cardiovascular diseases associated with poor psychosocial working conditions are common and are determined by a combination of work-related and non-work-related factors. Exposure surveillance provides better and more timely information to guide preventive intervention, particularly for work-related disease,20 yet remains under-utilised by governments including occupational health regulators 21 22. Although data on psychosocial working conditions is being included in a growing number of government and other surveillance systems internationally,23 there are relatively few published time trend studies24 25 and limited consideration of health disparities perspectives in the analyses reported 26…”
Section: Introductionmentioning
confidence: 99%
“…It is not feasible to rely on health outcome surveillance in this context as the mental disorders and cardiovascular diseases associated with poor psychosocial working conditions are common and are determined by a combination of work-related and non-work-related factors. Exposure surveillance provides better and more timely information to guide preventive intervention, particularly for work-related disease,20 yet remains under-utilised by governments including occupational health regulators 21 22. Although data on psychosocial working conditions is being included in a growing number of government and other surveillance systems internationally,23 there are relatively few published time trend studies24 25 and limited consideration of health disparities perspectives in the analyses reported 26…”
Section: Introductionmentioning
confidence: 99%
“…Still another aspect is if national exposure databases in different countries are collected and used for exposure surveillance and used in that way to improve workers' health. (5) One approach to improve the current situation is to introduce simple models in workplaces to help identify and characterize possible risks, such as the EASE (Estimation and Assessment of Substance Exposure) model, developed and maintained by Health and Safety Executive, UK. (6) It was originally developed to evaluate new and existing chemicals as required by European Union legislation.…”
mentioning
confidence: 99%
“…(7) The task and job title summaries presented emphasized description of who was doing what sort of cleanup work. (8) Generalizability (9;11) For example, a related report showed that one task among the 11 associated with beryllium is associated with the highest exposure levels: the cleanup task of "sorting, packaging, and repackaging of waste materials" in which beryllium dusts can be resuspended.…”
Section: Discussionmentioning
confidence: 99%